2011
DOI: 10.1590/s0100-879x2011007500100
|View full text |Cite
|
Sign up to set email alerts
|

Strength and power training did not modify cardiovascular responses to aerobic exercise in elderly subjects

Abstract: Resistance training increases muscle strength in older adults, decreasing the effort necessary for executing physical tasks, and reducing cardiovascular load during exercise. This hypothesis has been confirmed during strength-based activities, but not during aerobic-based activities. This study determined whether different resistance training regimens, strength training (ST, constant movement velocity) or power training (PT, concentric phase performed as fast as possible) can blunt the increase in cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 31 publications
2
29
0
1
Order By: Relevance
“…The interval between exercise series, cited in 11 studies, ranged from 30 seconds to 3 minutes, with no predominance of a specific interval (Table 2). Only two articles cited the speed of execution (2"X2") 11,18 (a result not shown in the table). In the specific case of TRT, the BMI values showed significant reductions in 2 articles 10,27 , while in 7 other articles 11,13,14,16,17,25,35 they were unchanged.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The interval between exercise series, cited in 11 studies, ranged from 30 seconds to 3 minutes, with no predominance of a specific interval (Table 2). Only two articles cited the speed of execution (2"X2") 11,18 (a result not shown in the table). In the specific case of TRT, the BMI values showed significant reductions in 2 articles 10,27 , while in 7 other articles 11,13,14,16,17,25,35 they were unchanged.…”
Section: Resultsmentioning
confidence: 99%
“…This variation in TRT studies may be explained by the fact that this training model does not permit aerobic exercise, which is a type of exercise that reduces the percentage of BF 18 , indicating that aerobic training is significantly better than TRT for the reduction of fat mass 25 . Analysis of BMI equivalent values revealed that in seven of the 16 TRT studies 11,13,14,16,17,25,35 the BMI did not change and in five 12,18,19,28,29 it increased. This behavior may be explained by the fact that TRT induces significant strength gains associated with muscle hypertrophy, which increase fat-free mass 18 .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Machado et al [30] investigated the behavior of heart rate and heart rate variability during different loads of resistance exercise (incline bench press) in ten patients with coronary artery disease vs. ten healthy sedentary controls and conclude that loads up to 30% one-repetitionmaximum during incline bench press, result in depressed vagal modulation in both groups, although only the coronary artery disease patients presented sympathetic overactivity at 20% one-repetition-maximum upper limb exercise. Kanegusuku et al [31] determined in 30 older adults whether different resistance training regimens, strength training (constant movement velocity) or power training (concentric phase performed as fast as possible) can blunt the increase in cardiovascular load during an aerobic stimulus and conclude that neither strength nor power training blunted submaximal or maximal heart rate, Systolic blood pressure or the rate-pressure product during the maximal exercise test, showing that they did not reduce cardiovascular stress during aerobic tasks. Mainenti et al [32] investigated the effects of levothyroxine on cardiopulmonary exercise reserve and recovery in 23 women with subclinical hypothyroidism submitted to two ergospirometry tests, with an interval of 6 months of normalization of thyroid-stimulating hormone levels (levothyroxine replacement group) or simple observation.…”
Section: Kk and Rocha E Silva M -Cardiology In Brazilian Scientific Joumentioning
confidence: 99%